Label-free detection of glycated haemoglobin in human blood using silicon-based photonic crystal nanocavity biosensor. Issue 13 (19th July 2016) - Olyaee, Saeed; Seifouri, Mahmood; Mohsenirad, Hamideh
Abstract: In this paper, we describe a two-dimensional photonic crystal-based biosensor that consists of a waveguide and a nanocavity with high sensitivity. A new method is employed for increasing sensitivity of the biosensor. The simulation results show that biosensor is highly sensitive to the refractive index (RI) variations due to injected biomaterials, like glycated haemoglobin, into the sensing surface. The proposed biosensor is designed for the wavelength range of 1514.4–1896.3 nm. The sensitivity and the quality factor are calculated to be 3000 and 272.43 nm/RIU, respectively. The designed structure can detect a 0.002 change in the RI via resonant wavelength shift of 0.9 nm. The band diagram and transmission spectra are computed using plane wave expansion and finite difference time domain methods.